Betonarme Elemanlarda Donatı Düzenleme İlkeleri - Sümer, Gözde (Fen Bilimleri Enstitüsü, 2009)
Yüksek Lisans tezi olarak sunulan bu çalışmada betonarme yapıların yük altındaki deformasyon biçimleri ile beraber davranış bilgisi, donatı düzenleme ilkeleri ve konstrüktif bilgiler her yapı elemanı için ayrı ayrı ele alınarak incelenmiştir. Donatı düzenleme kuralları TS 500 ve D.B.Y.B.H.Y ne paralel olarak belirtilmiştir. Malzeme bilgisi olarak beton, betonarme, betonarme yapı sistemleri ve derzler hakkında bilgiler verilmiştir. Betonarme ve davranış bilgisi, aderans, kenetlenme ve eklemeler, bazı önemli donatılar ve kolonlar, kirişler, döşemeler, temeller, perdeler, merdivenler ve istinat duvarları, donatı düzeninde özel durumlar, yüksek kirişler ve kısa konsollar incelenmiştir. Ayrıca donatı düzenlemelerine uyulmadığı takdirde karşılaşabilecek genel hasar türleri fotoğraflar ile sergilenmiştir. Sonuç olarak ise donatı düzeninde dikkat edilmesi gereken noktalar vurgulanmıştır.

In this master study firstly the deformation of the element under load, secondly the detailing requirements of the reinforcement in the element and thirdly the behaviour concept and constructive information of the structural element under load have been investigated individually. The detailing requirements, in the reinforced concrete structural elements are investigated together with the reasons and behaviour concept. The detailing requirements are pointed parallel with the TS 500 and Specification for structures to be built in Disaster Areas. Material information on concrete, concrete structures and jointings, concrete and concrete behaviour; bond, splice and binders; columns, beams, slabs, shear walls, partition walls, staircases and retaining walls, special cases in the detailing of reinforcement, high beams and short length chests are pointed in the study. General damage types, that may occur unless the detailing reinforcement principles are obeyed, are demonstrated via photographs. Lastly the basic points that are crucial in the detailing reinforcement are given.
Reinforcement Detailing Requirements For The Reinforced Concrete Structures
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: Donatı Düzenleme; Betonarme; Reinforcement detailing; Reinforced concrete